Pengaruh Skularisme Bagi Politik Indonesia - Harahap, Aprilinda M.; Soli, M Fahri Angga; Pratama, Bayu; Marbun, Syahrina Hayati; Suteja, Juliadi; Lubis, M. Rizki Haidir; Harahap, Desi Sapitri (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
Secularism is an understanding that only prioritizes material things and separates the life of the world and the hereafter, even this understanding always fights for the right to be free from various rules of religious teachings, they believe that all decision activities which are entirely located and made by humans, are not there may be a role and interference of religion in it. Secularism is an ideology that initially developed in the Western world and then continues to spread to almost all corners of the world, including the Islamic world and Indonesia in particular. This paper examines the relationship between religion and the state from the perspective of Islamic thought. This study aims to describe how the relationship between religion and the state in the Islamic view. The method used in obtaining data is descriptive method through library research. The principle of secularism in this case is that both theism and atheism cannot be proven by experience, so that it is outside the thought of secularism. Theology provides an interpretation of an unknown world while secularism does not want this kind of world and its interpretations at all. Thus secular is the nature of releasing this world from religion. For that we need a process, and this process is called secularization. Indonesia as a pluralistic country, on the one hand has a majority Muslim population even though other religions grow and develop dynamically in this archipelago. So that in a practical order it gives birth to a secular statehood concept where Islam is not used as the main principle in structuring the life of the nation and state. Keywords: Secularism, Influence, Politics, and Indonesia